2021
DOI: 10.3389/fmed.2021.761804
|View full text |Cite
|
Sign up to set email alerts
|

Potential Value of Expiratory CT in Quantitative Assessment of Pulmonary Vessels in COPD

Abstract: Objective: To investigate the associations between intrapulmonary vascular volume (IPVV) depicted on inspiratory and expiratory CT scans and disease severity in COPD patients, and to determine which CT parameters can be used to predict IPVV.Methods: We retrospectively collected 89 CT examinations acquired on COPD patients from an available database. All subjects underwent both inspiratory and expiratory CT scans. We quantified the IPVV, airway wall thickness (WT), the percentage of the airway wall area (WA%), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The emphysema had a greater impact on expiratory IPVV, and IPVV difference and relative values. However, Cao found that compared with LAA-950, the airway wall thickness had a more significant effect on expiratory IPVV and IPVV difference and relative values, 24 suggesting further exploration of the pathophysiology of the effects of emphysema and small airway disease on pulmonary blood vessels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The emphysema had a greater impact on expiratory IPVV, and IPVV difference and relative values. However, Cao found that compared with LAA-950, the airway wall thickness had a more significant effect on expiratory IPVV and IPVV difference and relative values, 24 suggesting further exploration of the pathophysiology of the effects of emphysema and small airway disease on pulmonary blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Cao also found that expiratory IPVV increased with COPD severity, and the difference decreased from the inspiratory phase, which were consistent with the findings of this study. 24 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, these methods rely on obtaining local and global labels, which can be difficult and subjective to acquire. Moreover, previous DL methods have primarily focused on utilizing a single CT image during full inspiration, neglecting the potential benefits of incorporating full expiration CT scans as surrogate markers for small-airway inflammation [ 11 , 12 ]. While large-scale cohort studies include expiratory CT scans for this purpose, their value for DL methods in COPD diagnosis has not yet been explored.…”
Section: Introductionmentioning
confidence: 99%